Prophet of blood - Tremayne, Peter (Tremayne, Peter. Sister Fidelma novels., 2024)
Autumn, AD 672. While out walking, Abbot Brocc was shocked to encounter the sinister apparition of a young woman, cloaked entirely in grey, who foretold his impending death. Dismissing the soothsayer's words, Brocc nevertheless felt concerned enough to ask for Sister Fidelma's advice on the matter. But by the time Fidelma and her companions arrive at the remote abbey of Dair Inis, Brocc has been found dead in the abbey's sweat house--as the mysterious prophetess had predicted. Plunged into a world of uncertainty, where believers of the Old and New Faiths are violently opposed, Fidelma, Eadulf and Dego embark on a journey fraught with danger, in a puzzling and perilous quest for the truth behind Brocc's murder. -- Provided by publisher.